2020
DOI: 10.1017/s0022377820000987
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid simulation of NBI fast-ion losses due to the Alfvén eigenmode bursts in the Large Helical Device and the comparison with the fast-ion loss detector measurements

Abstract: The multiphase simulations are conducted with the kinetic-magnetohydrodynamics hybrid code MEGA to investigate the spatial and the velocity distributions of lost fast ions due to the Alfvén eigenmode (AE) bursts in the Large Helical Device plasmas. It is found that fast ions are lost along the divertor region with helical symmetry both before and during the AE burst except for the promptly lost particles. On the other hand, several peaks are present in the spatial distribution of lost fast ions along the diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…MEGA has been successfully used to study wave-particle interactions in multiple tokamaks [22][23][24][25][26] as well as the LHD. [27][28][29][30] In this work, an m=n ¼ 1=1 EIC mode is not observed, which may be due to the fixed boundary condition chosen or other effects that will be investigated in a later study. This Letter is instead focused on the destabilization of an m=n ¼ 2=1 mode, closer to the plasma center than the EIC, by an anisotropic population of energetic particles in a high-performance deuterium LHD plasma.…”
mentioning
confidence: 87%
“…MEGA has been successfully used to study wave-particle interactions in multiple tokamaks [22][23][24][25][26] as well as the LHD. [27][28][29][30] In this work, an m=n ¼ 1=1 EIC mode is not observed, which may be due to the fixed boundary condition chosen or other effects that will be investigated in a later study. This Letter is instead focused on the destabilization of an m=n ¼ 2=1 mode, closer to the plasma center than the EIC, by an anisotropic population of energetic particles in a high-performance deuterium LHD plasma.…”
mentioning
confidence: 87%
“…A study of energetic ion loss due to the toroidal Alfvén eigenmode showed that the dominant loss process changed according to the plasma center position due to the change of energetic ion orbit and eigenfunction of the toroidal Alfvén eigenmode [22]. Comparing experimental results and the numerical simulation results revealed the loss process of beam ions due to the Alfvén eigenmode [23,24].…”
Section: Introductionmentioning
confidence: 94%